Interactions of Spring Cereal Genotypic Attributes and Recovery of Grain Yield After Defoliation - Bell, Lindsay W.; Kirkegaard, John A.; Tian, Lihua; Morris, Sally; Lawrence, John (Frontiers in Plant Science, 2020)
Dual-purpose crops are grazed during their vegetative phase and allowed to regrow to produce grain. Grazing slow-developing winter cereals (wheat, barley, and triticale) is common, but there is also potential to graze faster-developing spring cereals used in regions with shorter- growing seasons. Defoliation in faster-developing genotypes has risks of larger yield penalties, however, little is known about genotypic characteristics that may improve recovery after grazing. Four experiments examined 7 spring wheat and 2 barley cultivars with differing physiological attributes (phenological development rate, putative capacity to accumulate soluble carbohydrates, and tillering capacity) that may influence the capacity of spring wheat to recover after defoliation. Defoliated and undefoliated crops were compared to assess physiological differences between cultivars including recovery of biomass, leaf area and radiation interception at anthesis, and subsequent crop grain yield and yield components. All genotypes had similar responses to defoliation treatments indicating that the physiological attributes studied played little part in mitigating yield penalties after defoliation. Despite some differences in yield components amongst cultivars, defoliation did not adversely affect cultivars with different yield component combinations under non-water limited conditions. Later and intense defoliation (around GS30/31) resulted in large yield penalties (40%) which reduced both grain number and grain size. However, earlier defoliation (before GS28) induced small or insignificant yield penalties. Defoliation often reduced canopy radiation interception and crop biomass at anthesis but this rarely translated into large yield penalties. These studies further demonstrate that shorter season spring cereals can provide valuable forage (up to 1.2 t DM/ha) for grazing during early vegetative growth without inducing large yield penalties. This study suggests that beyond appropriate phenology, there were no other specific characteristics of cultivars that improved the recovery after grazing. Hence farmers don’t need specific dual-purpose cultivars and can still focus on those that optimise grain yield potential for a particular environment and sowing date. The timing and intensity of defoliation appear to be larger drivers of yield recovery in spring cereals and better understanding these relationships are needed to provide grazing management guidelines that mitigate risk of yield penalties in dual-purpose cereal crops.